Changes in cecal morphology, cell proliferation, antioxidant enzyme, volatile fatty acids, lipopolysaccharide, and cytokines in piglets during the postweaning period - Deng, Qingqing (J Anim Sci, 2020)
Weaning stresses often induce markedly structural and functional changes in the small intestine. However, little data are available on the changes of the morphology, function, and health in the cecum of piglets post-weaning. This study was conducted to measure the effects of weaning on the cecum in piglets. Forty piglets were weaned at 21 d and samples were collected at different time points (days 0, 1, 3, 7, and 14) post-weaning. The crypt depth, crypt width, and total epithelial cell numbers increased on days 7 and 14, compared with days 0, 1, and 3 (P < 0.001). The value of Ki67/total epithelial cells was highest on day 0 compared with all other days (P < 0.05). Besides, a higher concentration of malondialdehyde was observed on day 3 (P < 0.001). The activity of CuZn-superoxide dismutase (P < 0.05) enhanced from day 0 to 1 and the activity of catalase increased from day 1 to 3 (P < 0.001). In addition, days 3, 7, and 14 had greater acetic, propanoic, and butyric acid contents than on day 1 (P < 0.001). The pH and monocarboxylate transporter 1 (MCT1) expression increased from day 0 to 1 and from day 3 to 7 and decreased between days 1 and 3 (P < 0.001). The mRNA expression of solute carrier family 9 member A3 (SLC9A3) decreased on day 1 compared to all other postweaning days (P < 0.05). The abundance of toll-like receptor 4 (TLR4) and interferon-γ (IFN-γ) mRNA expression increased (P < 0.05) during the first 24 h after weaning. The concentration of lipopolysaccharide increased from day 3 to 7, then decreased on day 14 (P < 0.05). The mRNA expression of tumor necrosis factor-α (TNF-α) enhanced from day 7 to 14 (P < 0.05). The abundance of phosphorylated mammalian target of rapamycin protein was lower on day 14 than day 0 (P < 0.05). Taken together, these results show that weaning in piglets influences intestinal morphology, function, and health in the cecum.